Conservation and Utilization of Plant Genetic Resources - Rao, K. E. Prasada; Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
Germplasm and genetic resources are synonymous. Germplasm implies the sum total of hereditary material in a crop species along with its wild and weedy relatives. Land races are primitive varieties, which had evolved without any systematic selection effort. Obsolete varieties are those developed mostly by pure line and mass selection from the local cultivars of past but are no more grown. Various activities involved in the conservation of germplasm are described in this paper along with the trends in utilization of germplasm of some major crops and their significant achievement in plant breeding.